Features of Staphylococcus Aureus Antibiotic Sensitivity in Children with Atopic Dermatitis - Nikolay N. Murashkin; Alexander I. Materikin; Roman V. Epishev; Maria A. Leonova; Leonid A. Opryatin; Roman A. Ivanov; Alena A. Savelova (Вопросы современной педиатрии)
Background. Excessive colonization of the skin by various bacteria and fungi can be noted in patients with atopic dermatitis (AD), and the prevalence of secondary infection complications 30–48%. Several studies have shown that Staphylococcus aureus colonization is 60–100% in patients with AD compared to 5–30% in healthy persons from the control group. Moreover, the incidence of methicillinresistant Staphylococcus aureus (MRSA) isolates is up to 10–30% in skin cultures at AD, according to experts. Therapy of AD complicated by secondary infection is one of the crucial challenges of modern dermatology. Mupirocin can be considered as one of the most effective topical antibiotic among others used for etiotropic therapy of infectious complications in AD patients, and it has been confirmed by numerous clinical studies.Conclusion. Staphylococcus aureus is the most common trigger of AD aggravation. MRSA in AD complicated by secondary infection is difficult to manage as it becomes resistant to many types of antibiotics; however, it shows persistent sensitivity to mupirocin. Mupirocin-based (2%) external agent is the most effective, safe, and preferred therapy variant for AD complicated by secondary infection in pediatrics.